The effect of using a sports application on the quality of sleep in patients with heart failure: a randomized clinical trial study - Mohsen Arezomand; Mahlagha Dehghan; Zahra Ebrahimi Rigi; Farhad Fatehi; Parvin Mangolian Shahrbabaki (BMC, 2024)
Abstract Background Patients with heart failure often suffer from sleep disorders. Due to the side effects of medications used to treat this disorder, non-pharmacological methods may be used to improve these patients' sleep quality. This study aimed to determine the effect of a sports application on sleep quality in patients with heart failure. Methods In this single-blinded randomized clinical trial, 60 patients aged 30-70 referred to Shafa Hospital in Kerman were randomly assigned to control (n = 30) and intervention (n = 30) groups based on convenience sampling. The intervention group used the sports application for eight consecutive weeks. Data was collected using a demographic questionnaire and the Pittsburgh Sleep Quality Index (PSQI). An independent t-test and a Mann-Whitney U test were used for comparisons between groups and paired t-tests and Wilcoxon tests were used for comparisons within groups. Results The data analysis revealed a significant difference in sleep quality scores between the two groups after the intervention, meaning that the intervention group had better sleep quality than the control group (P < 0.05). Conclusions As a result of the study, it was found that the sport application improved the quality of sleep in patients with heart failure. Our recommendation is for healthcare providers to use this sports application to present educational content related to physical activity and improve the sleep quality of patients. Trial registration Iranian Registry of Clinical Trials: IRCT. 2019123045475N1." Registered 16 December 2019.